International comparison of treatment strategy and survival in metastatic gastric cancer. Issue 1 (9th October 2018) - Claassen, Y. H. M.; Bastiaannet, E.; Hartgrink, H. H.; Dikken, J. L.; de Steur, W. O.; Slingerland, M.; Verhoeven, R. H. A.; van Eycken, E.; de Schutter, H.; Lindblad, M.; Hedberg, J.; Johnson, E.; et al.
Abstract : Background: In the randomized Asian REGATTA trial, no survival benefit was shown for additional gastrectomy over chemotherapy alone in patients with advanced gastric cancer with a single incurable factor, thereby discouraging surgery for these patients. The purpose of this study was to evaluate treatment strategies for patients with metastatic gastric cancer in daily practice in five European countries, along with relative survival in each country. Methods: Nationwide population‐based data from Belgium, Denmark, the Netherlands, Norway and Sweden were combined. Patients with primary metastatic gastric cancer diagnosed between 2006 and 2014 were included. The proportion of gastric resections performed and the administration of chemotherapy (irrespective of surgery) within each country were determined. Relative survival according to country was calculated. Results: Overall, 15 057 patients with gastric cancer were included. The proportion of gastric resections varied from 8·1 per cent in the Netherlands and Denmark to 18·3 per cent in Belgium. Administration of chemotherapy was 39·2 per cent in the Netherlands, compared with 63·2 per cent in Belgium. The 6‐month relative survival rate was between 39·0 (95 per cent c.i. 37·8 to 40·2) per cent in the Netherlands and 54·1 (52·1 to 56·9) per cent in Belgium. Conclusion: There is variation in the use of gastrectomy and chemotherapy in patients with metastatic gastric cancer, and subsequent differences in survival. Abstract : The purpose of this study was to evaluate the treatment strategy for patients with metastatic gastric cancer in daily practice in five European countries. Relative survival in each country was also determined. Variation in the use of a gastrectomy for patients with metastatic gastric cancer across Europe was found together with wide variation in chemotherapy use for the two countries with data on chemotherapy. NA, Not applicable (not recorded in the Danish and Norwegian cancer registries, and limited recording in the Swedish cancer registry). Survival probably influenced by variation in treatments